Prevalence, Antimicrobial Resistance, and Virulence Potential of Staphylococcus aureus in Donkeys from Nigeria - Onyinye Josephine Okorie-Kanu; Madubuike Umunna Anyanwu; Obichukwu Chisom Nwobi; Regina Yaya Tambe-Ebot; Nkechi Harriet Ikenna-Ezeh; Chukwuemeka Calistus Okolo; Lynda Onyinyechi Obodoechi; Patience Chinasa Ugwu; Ifeyinwa Riona Okosi; Ishmael Festus Jaja; James Wabwire Oguttu (Antibiotics)
Background: Animal-associated antimicrobial-resistant staphylococci pose a One Health concern, as they can spread into the environment and cause serious infections. Yet, donkeys in Nigeria have been largely overlooked as potential reservoirs of these pathogens. Aim/Objectives: To isolate Staphylococcus aureus from donkeys in Obollo-Afor, southeast Nigeria, assess their antimicrobial resistance profiles, and evaluate their virulence potential. Materials and Methods: Staphylococci were isolated from the nasal swabs of 250 donkeys, using mannitol salt agar, confirmed biochemically, with Staphylococcus aureus identified via a latex agglutination test and mass spectrometry. The resistance profiles of the isolates, including in regard to methicillin, inducible clindamycin, and β-lactamase production, were determined using disc diffusion, while vancomycin resistance was assessed through the use of agar dilution. The virulence factors were evaluated phenotypically. Results: Of the 250 samples, 11 (4.4%) contained S. aureus and 239 (95.6%) grew other Staphylococcus species. The resistance rates of the 11 S. aureus isolates to gentamicin, penicillin, tigecycline, cefoxitin, linezolid, and chloramphenicol were 45.5%, 66.7%, 54.5%, 27.3%, 36.4%, and 18.1%, respectively. The phenotypic methicillin-resistant S. aureus prevalence was 1.2%. Additionally, 23.5% of the S. aureus isolates were multidrug resistant, with a mean antibiotic resistance index of 0.25. All the S. aureus isolates exhibited virulence factors like clumping factor expression, catalase, caseinase, lecithinase, and gelatinase activity, while the occurrence of haemagglutinin, biofilm, pellicle, and hemolysin occurred in 27.3%, 54.5%, 36.4%, 72.2%, respectively. Conclusion: Although a small percentage of donkeys in Nigeria may harbor S. aureus, these animals are potentially spreading antimicrobial resistance, including multidrug and methicillin resistance, to humans and the environment.